Amphipathic compound, preparation method therefor, and surfactant composition comprising same (European Patent Office Munich, 2024)
The present invention relates to an amphipathic compound, a preparation method therefor, and a surfactant composition comprising same and, specifically, to a compound selected from the group consisting of steviol monoglycoside-acid, steviol monoglycoside-ester, and steviol monoglycoside-amide, a preparation method therefor, and a surfactant composition comprising at least one of these compounds.